Profile of Obesity and Comorbidities in Elderly Patients with Heart Failure - Dădârlat-Pop A (Dove Medical Press, 2020)
Alexandra Dădârlat-Pop,1 Adela Sitar-Tăut,2 Dumitru Zdrenghea,3 Bogdan Caloian,3 Raluca Tomoaia,1 Dana Pop,3 Anca Buzoianu4 1Cardiology Department, "Iuliu Haţieganu" University of Medicine and Pharmacy, Cluj-Napoca, Romania; 2Internal Medicine Department, 2nd Department, Medical Clinic IV, Cluj-Napoca, Romania; 3Internal Medicine Department, Cardiology - Rehabilitation Department, Clinical Rehabilitation Hospital, Cluj-Napoca, Romania; 4Department of Pharmacology, Toxicology and Clinical Pharmacology, "Iuliu Haţieganu" University of Medicine and Pharmacy, Cluj-Napoca, RomaniaCorrespondence: Dana Pop Email pop67dana@gmail.comBackground and Purpose: In Romania, robust data about the prevalence of obesity and heart failure are lacking, especially in the elderly; therefore, this study aims to analyze the profile of overweight and obese patients aged > 65 years admitted to a Romanian hospital for worsening heart failure, and also their risk in the presence of comorbidities.Patients and Methods: This cross-sectional study was conducted in 126 consecutive elderly patients with overweight and obesity admitted to a Romanian hospital for worsening heart failure. They were divided into three groups: with reduced (< 40%) – HFrEF, mid-range (40– 49%) – HFmrEF and preserved (≥ 50%) ejection fraction – HFpEF. Obesity was defined according to the body mass index (BMI) status: obesity, ≥ 30 kg/m2; overweight, 25– 29.9 kg/m2. The Charlson Comorbidity Index (CCI) was calculated to evaluate the severity of comorbidity, with a score ranging from 2 (only heart failure present and age > 65 years) to 30 (extensive comorbidity).Results: NT-proBNP values are negatively correlated with BMI only in patients with HFpEF. Creatinine clearance (p=0.0166), the presence of atrial fibrillation (p=0.0095) and NYHA functional class were independent predictors of increased NT-proBNP values. CCI score is negatively correlated with NT-proBNP values in patients with HFmrEF (r= − 0.448, p=0.009) and HFpEF (r= − 0.273, p=0.043). The CCI risk was not significantly different between the three groups.Conclusion: Elderly heart failure patients with overweight or obesity have particular characteristics in terms of NT-proBNP values and presence of comorbidities. In the studied population, NT-proBNP levels were strongly influenced by renal function, NYHA functional class, the presence of atrial fibrillation and left ventricular ejection fraction.Keywords: obesity, heart failure, comorbidity, elderly patients